Mecanismos de previsão da atividade econômica brasileira em cenários distintos de volatilidade - Pinto, Vitor Hugo Gaspar (2017)
This paper aims to forecast the economic activity or growth of Brazil's Gross Domestic Product (GDP) using AR, ARMA and VAR models with monthly data between January 2002 and December 2016 and considering different volatility environments. The results indicate that volatility is important to explain the ability of econometric models, since the prediction errors were larger in scenarios of greater instability. In comparative terms, there is no statistically significant difference between the predictive abilities of the best models in the environment of lower volatility and the VAR model (2) was distinguished by presenting the best prognostics in situations of greater instability.